ECONOMIC POTENTIAL OF WAQF FOR SOCIAL WELFARE: PATTERNS AND CONTRASTS IN MENAP AND COUNTRIES IN SUB-SAHARAN AFRICA - Hariri, Mohammad (International Journal of Sukuk and Waqf Research, 2023)
The Waqf has become a matter of increasing priority for Islamic scholars and policymakers, given its potential as a mechanism for the socioeconomic advancement of Muslim communities worldwide. This systematic literature review investigated the critical economic and social dimensions of the Waqf in the Middle East, North Africa, and Pakistan (MENAP) region and predominantly Muslim nations of sub-Saharan Africa. Through a rigorous examination of academic databases, 61 relevant primary sources published since 2014 were analyzed using thematic analysis techniques to uncover patterns and contrasts in managing and utilizing the Waqf across countries. The findings reveal significant diversity in Waqf economic strategies implemented, with greater uptake of Cash Waqf and Waqf-based microfinance in MENAP countries compared to sub-Saharan Africa, where adoption is limited. Approaches also diverge regarding the investment of Waqf assets in financial products, with higher prevalence in the Gulf countries than elsewhere. In the social dimension, Waqf has funded traditional educational institutions in MENAP, but the innovation support is largely untapped. Health care and affordable housing are recurring areas of Waqf’s contribution, but the impact is uneven: countries like Kuwait and Qatar show more advanced development than Yemen. Women’s economic empowerment through the Waqf is more pronounced in the Gulf region than in countries like Nigeria. The review identifies gaps in understanding Waqf’s performance in various countries, best practices, and underlying drivers, setting out a roadmap for further comparative research to unlock Waqf’s potential as an inclusive development tool.